2015
DOI: 10.1002/ejp.720
|View full text |Cite
|
Sign up to set email alerts
|

Rutin antinociception involves opioidergic mechanism and descending modulation of ventrolateral periaqueductal grey matter in rats

Abstract: Our results provide evidence that rutin produces antinociceptive effects involving central modulation of the vlPAG descending circuit partly mediated by an opioidergic mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 56 publications
(65 reference statements)
2
17
0
Order By: Relevance
“…Substantially, EA-induced analgesia is a manifestation of integrative processes at different levels of the CNS between afferent impulses from the nociceptive regions and impulses from the acupoints [ 9 ]. The periaqueductal gray (PAG) with the various neurons (e.g., opioidergic, serotonergic, GABAergic) [ 21 , 22 , 23 , 24 ] integrates ascending nociceptive or acupuncture signals from the SDH and the descending antinociceptive signals from amygdala, habenula nucleus and hypothalamus [ 25 , 26 , 27 , 28 , 29 ]. Then, integrated signals were delivered to the rostral ventromedial medulla, locus coeruleus and SDH for modulating central homeostasis and responding to nociceptive stimuli [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Substantially, EA-induced analgesia is a manifestation of integrative processes at different levels of the CNS between afferent impulses from the nociceptive regions and impulses from the acupoints [ 9 ]. The periaqueductal gray (PAG) with the various neurons (e.g., opioidergic, serotonergic, GABAergic) [ 21 , 22 , 23 , 24 ] integrates ascending nociceptive or acupuncture signals from the SDH and the descending antinociceptive signals from amygdala, habenula nucleus and hypothalamus [ 25 , 26 , 27 , 28 , 29 ]. Then, integrated signals were delivered to the rostral ventromedial medulla, locus coeruleus and SDH for modulating central homeostasis and responding to nociceptive stimuli [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…As part of an attempt to establish the antinociceptive potential of D. linearis and to promote the use of medicinal plants as pain-relieving agent, MEDL was also subjected to phytoconstituents analyses using the UHPLC-ESI-HRMS and GC-MS methods to determine the presence of polyphenolics or any volatile bioactive compounds with potential antinociceptive activity, respectively. The UHPLC-ESI-HRMS analysis of MEDL leads to identification of approximately 30 polyphenolic compounds of which several of them, such as gallic acid [60,61], ferulic acid [62], protocatechuic acid [63], caffeic acid [64,65], p-coumaric acid [66], rutin [67,68], isoquercitrin [69], astragalin [70], catechin [71], quercetin [72,73], apigenin [74] and kaempferol [75], have been reported to show antinociceptive activity. These reports also revealed that: (i) gallic acid was reported to show low antinociceptive activity against the acetic acid-induced nociception [60] while its derivative (gallic acid ethyl ester) was reported to attenuate bradykininand formalin-induced nociception [61].…”
Section: Discussionmentioning
confidence: 99%
“…These reports also revealed that: (i) gallic acid was reported to show low antinociceptive activity against the acetic acid-induced nociception [60] while its derivative (gallic acid ethyl ester) was reported to attenuate bradykininand formalin-induced nociception [61]. In addition, gallic acid ethyl ester was ineffective in the hot-plate test and demonstrated partly the opioid/NO-independent action; (ii) ferulic acid exerts an opioid-mediated antinociceptive activity when assessed using the hot plate test [62]; (iii) protocatechuic acid also exerts an opioid-mediated antinociceptive activity when assessed using the hot plate test [63]; (iv) caffeic acid demonstrated the antinociceptive activity against the abdominal constriction test and the late phase of the formalin-induced nociception, but not the hot plate test [64] whereas the dodecyl ester derivative of caffeic acid were reported to produce antinociceptive activity against the abdominal constriction test as well as the formalin-, capsaicin-and glutamate-induced nociceptive model [65]; (v) rutin exerts antinociceptive activity when assessed using the abdominal constriction test and the formalin-induced nociception, respectively [66,67] with Hernandez-Leon et al [67] also showed that rutin produces an opioid-mediated antinociceptive activity only in the late phase of the formalin-induced test; (vi) isoquercitrin exhibits antinociceptive activity against the abdominal constriction and formalin tests [68]; (vii) astragalin demonstrates an opioid-mediated antinociceptive activity when assessed using the hot plate test and the formalin-induced nociception [69]; (viii) catechin produces antinociceptive activity against the abdominal constriction, hot plate and formalin-induced paw licking tests with an opioid-independent activity shown using the hot plate test [70]; (ix) quercetin was earlier reported to show an opioid-mediated antinociceptive activity when assessed using the hot plate test [71] while later study demonstrates that quercetin produces antinociceptive activity against the abdominal constriction test, as well as the formalin-, capsaicin-and glutamate-induced nociceptive tests that involves an interaction with l-arginine/NO pathway [72]; (x) apigenin was found to show antinociceptive activity against the abdominal constriction, hot plate and formalin-induced paw licking tests with the centrally-mediated opioid activity proven using the hot plate test [73]; and (xi) kaempferol derivatives (i.e., kaempferol 3-O-rutinoside, kaempferol 3-O-glucoside and kaempferol-3,7-di-O-α-l-rhamnopyranoside) was reported to exert antinociceptive activity against the abdominal constriction and formalin-induced paw licking tests [74,75]. In addition, Ali et al [75] also...…”
Section: Discussionmentioning
confidence: 99%
“…Chlorogenic acid has been involved in the antinociceptive effects of other species with this property (Küpeli et al 2012, Martínez-González et al 2016. In case of rutin, this flavonoid glycoside possesses antinociceptive properties mediated by central opioidergic neurotransmission (Selvaraj et al 2014, Hernandez-Leon et al 2016. This flavonoid has been even combined with a clinical analgesic to improve the efficacy against pain (Alonso- Castro et al 2017).…”
Section: Discussionmentioning
confidence: 99%